Optimalisasi Pekarangan Rumah sebagai Strategi Penguatan Ketahanan Pangan Rumah Tangga melalui Budidaya Cabai Rawit di Desa Slarang - Anzar Alfat Firdaus; Faiz Naufal Fahruddin; Bunga Lestari Kurniasih; Yasmine Zahra; Jenita Damayanti; Diva Maria; Endah Lestari Ningsih; Faiza Fidela Titananda; Alexander Mileoner Putra Waruwu; Rifqi 'Ainur Dynda Gunawan (Research Journal of Social Economics Empowerment, 2026)
Household food security in rural areas remains a challenge due to dependence on external food supplies and price fluctuations of horticultural commodities, particularly chili peppers. Slarang Village, Kesugihan Subdistrict, Cilacap Regency, has considerable home-yard potential that has not been optimally utilized to support household food independence. This community service activity aims to enhance the utilization of home yards through the intensification of chili seed planting as an effort to strengthen household food security. A qualitative descriptive approach was employed through field observations, interviews, mentoring, and hands-on practice of chili cultivation using polybags. The results indicate that home-yard intensification through chili cultivation improves community knowledge and skills in simple cultivation techniques and contributes to the availability of fresh food at the household level. This activity also has the potential to reduce household dependence on market supplies and mitigate household expenditures caused by chili price volatility. Therefore, home-yard intensification through chili cultivation represents an effective, practical, and sustainable strategy for strengthening village-level food security.